Fiscal dependence on extractive revenues: Measurement and concepts - Kyle McNabb (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
The aims of this paper are twofold. It firstly identifies and discusses the extent to which public revenues from natural resources are adequately captured in existing cross-country revenue databases, before exploring the extent to which such data can be used to estimate countries' fiscal dependence on extractives. I first discuss key conceptual, definitional and measurement issues, before comparing the coverage of key existing databases, notably the UNU-WIDER Government Revenue Dataset (GRD). I then propose a new measure of fiscal dependence on extractive revenues (FDE). Whilst a number of existing studies have attempted to better quantify countries' resource dependence, to the best of my knowledge none has yet proposed an indicator that ties the idea of dependence to any outcomes. The FDE simply calculates the extent to which extractive-producing countries can fund day-to-day government spending with non-extractive revenues. I find that the FDE is strongly correlated with existing measures of extractive dependence but can ultimately tell us more about countries' fiscal positions and resulting vulnerability to shocks to revenue or government spending.
Keywords: N5; P28; Q32; E62; 330; extractives; government revenues; taxation; resource curse